Planejamento tributário em micro e pequenas empresas do Amazonas - Silva, Jasse Muriel Santos (Brasil, 2024)
The research analyzes the use of tax planning by micro and small companies (MSEs), identifying the relationships between the use of this instrument and the perception of benefits, and impacts on the economic and financial performance of managers of companies of this size. The methodology used was quantitative, a survey with online questionnaires for managers/owners in Amazonas. The main results point to: (1) respondents have little to full knowledge about tax planning and its economic-financial impact on companies; (2) the majority of companies participating in the research do not use tax planning.